The association between healthy lifestyle behaviors and health‐related quality of life among adolescents - José J. Muros; Federico Salvador Pérez; Félix Zurita Ortega; Vanesa M. Gámez Sánchez; Emily Knox (Brazilian Society of Pediatrics, 2017)
Objective: The aim of this research was to examine the association between body mass index, physical activity, adherence to the Mediterranean diet, and health‐related quality of life in a sample of Spanish adolescents. Method: The study involved 456 adolescents aged between 11 and 14 years. They completed questionnaires on the Mediterranean diet (KIDMED), physical activity (Physical Activity Questionnaire for Older Children [PAQ‐C]), and quality of life (KIDSCREEN‐27). Body mass index was calculated. Hierarchical linear regression analyses were used to determine whether health‐related quality of life could be predicted by the measured variables. The variables were analyzed in a stepwise manner, with Mediterranean diet entered in the first step, body mass index in the second, and physical activity in the third. Results: Mediterranean diet accounted for 4.6% of the variance in adolescent's health‐related quality of life, with higher adherence to the Mediterranean diet predicting higher health‐related quality of life‐scores. Body mass index accounted for a further 4.1% of the variance, with a higher body mass index predicting lower health‐related quality of life scores. Finally, physical activity explained an additional 11.3% of the variance, with a higher level of physical activity being associated with higher health‐related quality of life scores. Together, these variables explained 20% of the variance in the adolescents' health‐related quality of life. Conclusions: Physical activity, body mass index, and adherence to the Mediterranean diet are important components to consider when targeting improvements in the health‐related quality of life of adolescents, with physical activity representing the component with the greatest influence.